Enzymatic cross-linking of soy proteins within non-fat set yogurt gel. Issue 3 (23rd July 2014) - Soleymanpuori, Rana; Madadlou, Ashkan; Zeynali, Fariba; Khosrowshahi, Asghar
Abstract : Soy proteins as the health-promoting ingredients and candidate fat substitutes in dairy products are good substrates for the cross-linking action of the enzyme transglutaminase. Non-fat set yogurt samples were prepared from the milks enriched with soy protein isolate (SPI) and/or treated with the enzyme transglutaminase. The highest titrable acidity was recorded for the yogurt enriched with SPI and treated with the enzyme throughout the cold storage for 21 d. SPI-enrichment of yogurt milk increased the water holding capacity. Although enrichment with SPI did not influence the count of Streptococcus themophilus, increased that of Lactobacillus bulgaricus ∼3 log cycles. The enzymatic treatment of SPI-enriched milk however, suppressed the bacteria growth-promoting influence of SPI due probably to making the soy proteins inaccessible for Lactobacillus . SPI-enrichment and enzymatic treatment of milk decreased the various organic acids content in yoghurt samples; influence of the former was more significant. The cross-linking of milk proteins to soy proteins was confirmed with the gel electrophoresis results.